Sobre as origens da diocese do Porto na Alta Idade Média. Uma reflexão sobre o Parochiale Suevorum e a diocese de Magneto/Meinedo (sécs. VI-VII). - Renzi, Francesco; Mariani, Andrea (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2020)
Traditionally, scholars considered Magneto/Meinedo as the originary See of Porto/Portucale in the 6th century. This conclusion grounds mainly on two sources: the Parochiale Suevorum and the acts of the II Council of Braga, where among the subscribers appears a «Viator Magnetensis ecclesiae episcopus». The analysis of the sources in their historical context and chronology show, however, a more complex and contradictory panorama. In this work, we will try to examine the different interpretations elaborated by scholars and to propose a reflection on both the Parochiale Suevorum and the relations between Meinedo and Porto between the Late Antiquity and the High Middle Ages. In order to achieve these objectives, we will first introduce the historiographical outcomes on this specific theme. Second, we will analyse and compare historiographical data to the information contained in both written sources and archaeological materials. Finally, we will advance some possible hypotheses to interpret the eventual connection between these two dioceses.